Production Engineering - Advantages of Flowing Wells through Tubing - Hallan N. Marsh; Bruce H. Robinson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
It is generally believed that the flowing of wells through tubing instead of casing results in the conservation of gas. It is further believed that use of tubing prolongs the flowing life of a well and results in greater ultimate recovery, provided either that there are no adjacent wells, or that any adjacent wells are similarly operated. Recent experience in the flowing of Buckbee zone wells at Santa Fe Springs has not only substantiated both of these beliefs but has led to the further conclusion that the use of tubing results in a greater cumulative flowing production, ' even in a highly competitive field like Santa Fe Springs, where the wells concerned are closely offset by wells of both the same and other companies flowing through casing. Further, gas-oil ratio has been so reduced that greater ultimate recovery can be expected. In the belief that such would be the case, the majority of the Buckbee zone wells of one company were brought in through tubing, but enough wells were flowed through casing to form the basis for a comparison. For the purpose of this comparison, wells with flow strings 2½ or 3-in. dia. are designated as tubed wells, while those having flow strings larger than 3-in. dia. are designated as untubed wells. Casing used was mostly of 5 ¾-in. dia., the remainder being of 4¾-in. dia. There were 15 tubed wells and 8 untubed wells and they were scattered over the field in such a way that neither group appears to have any distinct advantage as regards location. Locations of all wells involved in the comparison are shown on Fig. 1. All the Buckbee sand wells of the company are included in the average production curves, with the exception of eight that were unsatisfactory for reasons other than the method of flowing. Findings 1. Buckbee sand wells flowing through casing larger than 3 in. had an average maximum production rate of 4670 bbl. per day, while wells flowed through straight tubing or 3-in. casing had an average maximum production of only 3300 bbl. per day. (See Fig. 2.)